Economic Policy in a Highly Dollarized Economy : The Case of Cambodia. (Occasional Papers; Occasional Paper ;, 2003)
This study examines the challenges and issues facing policymakers in highly dollarized economies. Focusing on Cambodia, which achieved almost complete dollarization during 1991-95, the authors review recent developments in the literature on dollarization and examine the costs and benefits of dollarization in Cambodia, including the ensuing macroeconomic policy implications. They carry out an econometric estimation of cash foreign currency circulation in Cambodia in order to gauge the degree of dollarization. In addition to this analysis, the authors present a short description of Cambodia's economic, financial, and structural background.